Le «borie» vichiane come paradigma euristico. Hybris dei popoli e dei saperi fra moderno e contemporaneo - Rosario Diana (ed.) (I Quaderni del Lab, 2015)
The essays included in this volume assume Giambattista Vico's theory of the "conceits" (borie) as a heuristic paradigm for investigating different forms of arrogance by peoples and by kinds of knowledge. The book is made up of three sections. In the first one - "A possible Vichian paradigm" - Manuela Sanna's essay examines the theme of the conceits in Vico's writings, exploring it in all its ramifications. The essay by Giuseppe Cacciatore extrapolates the concept of conceit from Vico's page and turns it into an useful tool for unmasking "other" kinds of arrogance. In the second section - "A retrospective" - a possible backwards path is outlined: various expressions of arrogance by peoples and by kinds of knowledge are investigated in authors closer to Vico or even more distant from him, like Molina, Montaigne and Diodorus, who was among Vico's sources. The third section - "With Vico beyond Vico" - hosts contributions by scholars who tested the paradigm of the conceits in authors ranging from Descartes to Samuel Beckett. This results in a theoretical and historical framework that, without claiming to be exhaustive or organic, provides a varied and rich survey of the topic.